REKONTEKSTUALISASI PRAKTIK SOSIAL MEREJUNG DALAM NASKAH ULU PADA KELOMPOK ETNIK SERAWAI DI BENGKULU - Sarwit Sarwono; Ngudining Rahayu; Agus Joko Purwadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
AbstrakPenelitian ini bertujuan mendeskripsikan pengetahuan budaya dan praktik sosial merejung dalam tari adat pada kelompok etnik Serawai di Bengkulu. Sumber data penelitian adalah naskah-naskah Ulu, yakni MNB 07.18, MNB 07.30, dan MNB 07.70 (koleksi Museum Negeri Bengkulu). Penelitian ini berbasis filologi dan analisisnya didukung analisis wacana, khususnya discourse and practice. Ketiga teks dalam naskah ditransliterasi dengan menggunakan edisi kritis. Adapun data pengetahuan budaya dan praktik merejung dalam tari adat dikumpulkan melalui pengamatan dan wawancara di desa Ujung Padang dan Nanjungan di Kecamatan Semidang Alas, Kabupaten Seluma. Hasil penelitian sebagai berikut. Pertama, dalam ketiga naskah Ulu tertulis teks rejung (sejenis pantun) sebagaimana yang ditemukan dalam tradisi lisan yang biasa dibawakan secara berbalasan antara bujang dan gadis dalam tari adat pada bimbang (pesta) pernikahan. Kedua, sebagai wacana, ketiga teks Ulu merepresentasikan pengetahuan budaya dan praktik sosial merejung. Ketiga, sebagai wacana, ketiga teks merupakan transformasi dan rekontekstualisasi praktik sosial merejung dari kelompok etnik yang bersangkutan.Kata kunci: teks Ulu, rekontekstualisasi, transformasi, praktik sosial RECONTEXTUALIZATION OF THE SOCIAL PRACTICE OF MEREJUNG IN THE ULU MANUSCRIPT IN THE SERAWAI ETHNIC GROUP IN BENGKULUAbstractThis study aims to describe the cultural knowledge and social practice of merejung in the traditional dance in the Serawai ethnic group in Bengkulu. The data sources were Ulu texts, namely MNB 07.18, MNB 07.30, and MNB 07.70 (a collection of the State Museum of Bengkulu). The study was based on philology and the analysis was supported by discourse analysis, especially discourse and practice. The three texts in the manuscripts were transliterated using a critical edition. The data of the cultural knowledge and practice of merejung in the traditional dance were collected through observations and interviews in Ujung Padang and Nanjungan villages, Semidang Alas District, Seluma Regency. The findings are as follows. First, in the three Ulu manuscripts, rejung (a kind of pantun) texts are written as they are found in the oral tradition which is usually performed in an exchange between a boy and a girl in a traditional dance in a wedding bimbang (party). Second, as a discourse, all the three Ulu texts represent the cultural knowledge and social practice of merejung. Third, as a discourse, the three texts are the transformation and recontextualization of the social practice of merejung in the ethnic group concerned.Keywords: Ulu texts, recontextualization, transformation, social practice